Tuning of fluorescence efficiency via local modification of the crystal structure by benzyl groups in polymorphs of a pyrazine dye. Issue 14 (21st March 2017) - Akune, Yoko; Hirosawa, Risa; Endo, Natsuko; Hatano, Sayumi; Hosokai, Takuya; Sato, Hiroyasu; Matsumoto, Shinya
Abstract : Comparison of a new polymorph with other solid forms indicated that benzyl groups influenced the fluorescence efficiency of 2, 5-diamino-3, 6-dicyanopyrazine. Abstract : Polymorphism-dependent fluorescence, a phenomenon in which a compound shows various fluorescence properties among its polymorphs, contributes to understanding the relationship between the crystal structure and solid-state fluorescence properties. Here we report a variety of solid-state fluorescence efficiencies brought about by benzyl groups in polymorphs of an organic pyrazine dye, where the polymorphs showed quite different fluorescence efficiencies (fluorescence quantum yield: 14% vs. 64%) despite their similar molecular conformations and packing motifs in the crystal structures. Crystal structure analysis and optical measurements revealed that local loose packing caused by the benzyl groups, which are not a part of the pyrazine fluorophore, greatly influenced the fluorescence efficiency in the polymorphs. This result showed that a benzyl substituent can be used as an effective molecular modification for tuning solid-state fluorescence efficiency.